Return to training considerations post COVID-19 - Finnoff, J. (USOPC Guidance: Return to Training and Sport Event Planning, 2020)
The USOPC is dedicated to protecting the health and safety of Team USA. The purpose of this document is to provide athletes, coaches and sports organizations (including National Governing Bodies [NGBs]) with information they can use to assist them with developing their return to training programs in the context of COVID-19. As a guideline meant to be used by sports as varied as archery and judo in locations as diverse as Minot and New York City by athletes and organizations with vastly different resources, this document cannot be prescriptive; rather, it should spark thoughtful deliberation among athletes, coaches and staff, who will use this information to create their own unique return to training plan that is specific to their situation. Many of the recommendations rely upon rules and regulations set forth by public health authorities, which will be different across the country. In addition to the logistical challenges of returning to training following COVID-19, there are also ethical and societal considerations that are beyond the scope of this document. These include, but are not limited to: o When is the rate of community COVID-19 transmission, and therefore the risk of infection, low enough to allow group training or sharing of equipment? o Do current COVID-19 or viral serology tests have sufficient accuracy, provide enough information, and have adequate scientific evidence to be used to limit the risk of COVID-19 infection among those participating in group training? o Is it appropriate to use tests for athletics when there are shortages of tests for those who are sick? o Can you mandate athlete testing in order to train with a group? o Is it appropriate for athletes, coaches or staff to use personal protective equipment (PPE) meant for medical personnel when there is a worldwide shortage of PPE? o Should or can you restrict athletes from participating in practice if they arrive from a location with active community transmission of COVID-19? Finally, although the young and healthy tend to have less severe cases of COVID-19, every case of this disease is potentially life-altering or deadly, particularly in those with risk factors that may occur in our Olympic or Paralympic athletes such as asthma, hypertension, diabetes, liver disease, kidney disease, immune suppression, or neurologic disorders affecting respiration. Until COVID-19 is either eradicated, a vaccine is developed, or a cure is found, there is no way of completely eliminating the risk of fatal infection. This should always be in the forefront of your mind when designing your return to training program.